MUSEUMS OF SOVIET BELARUS IN THE YEARS OF CULTURAL REV OLUTION. 1928–1941 - Huzhalouski, Alexander A. (Acta Museologica Lithuanica, 2015)
Using a wide range of archival sources, periodicals and contemporary research, information on the transformation of Soviet Belarusian museums in the years of cultural revolution (1928–1941) is presented in this article. By 1928 a centralized museums system was established in Soviet Belarus consisted of state public museums subordinated to the People’s Commissar of Enlightenment Office, state museums subjected to various educational and research institutions and communal local lore museums coordinated by Central Bureau of Local Lore. The Soviet system of museum policy was revised in the 1930s, when Stalin further centralized the cultural sector by imposing the obligatory ideological pattern. Post-1930 development of Belarusian museums took place in a drastically different political, cultural and material context. The creating a new ‘Soviet man’entirely replaced ethnic nation-building. After museums at western Belarusian ethnic lands became a part of the Soviet Belarus in 1939 they underwent profound changes as well. Basic functions of all Soviet Belarusian museums were subjected to comprehensive change including the manner in which societal processes was documented, the interpretation of collections on display, and even analysis of visitor logs and feedback. Museums, which were considered one of the most important channels for educating the communist masses, attracted special attention from the Communist party ideologists and government officials. The author provides insight into the character of phenomenon of totalitarian museum which was one of key element of political propaganda machine set up by the Communist Party Central Committee.
Keywords: Cultural revolution; communist ideology; state museum policy; People’s Commissar of Enlightenment Office; Central Bureau of Local Lore; Belarusian State Museum; state public museums; communal local lore museums; museums of West Belarus